Estas vidas, por que não ir escutá-las lá de onde falam por si próprias? Diálogos com os membros das associações de catadores de materiais recicláveis de Vitória-ES - Pinheiro, Priscila Tinelli (2015)
This study analyzes the Pickers Association acting as a possible enhancement mechanism of fundamental rights to health, education and housing, which include as objectives of the National Waste Pickers Movement. It was adopted as the scientific method the dialectic accompanied by techniques of literature research and participant observation, whereby the researcher sought to get to know this social reality, and to establish a dialogue with the collectors. As a theoretical framework, we used the theories of Boaventura de Sousa Santos about the sociology of absences, with respect to the forms of production of non-existence, beyond the abyssal thinking to understand the existing tensions between the pickers and civil society and theoretical construction of Santos on social fascism which falls on society and divided according to the degree of exclusion suffered and accessibility of rights. Thus, we started from the approach of the processes of exclusion and social stigmatization to analyze the phenomenon of public invisibility and its consequences to the group of pickers. In the second part, it's introduced the legal invisibility faced by pickers, as well as the rise of the national movement as an important mechanism fight on the national stage and the main specificities of the rights to health, education and housing as fundamental social rights. Finally, there was the analysis - from the benchmark constructed by each of the pickers - about a possible improved access to fundamental rights, which is proved by the comparison with the situation of these people, but that is still far from ideal, because of the need of achievement for larger spaces, both in society and in the economic market for recyclable material collectors. The organization in solidarity enterprises is an important move against hegemonic front of the capitalist system empire, however the way, for this category, is still long in the realization of fundamental rights scenario.